Bibliometric analysis of imaging and treatment strategies for severe tricuspid regurgitation from 2015 to 2023 - Schlegl, Johannes; Bannehr, Marwin; Kücken, Tanja; Jankowska, Paulina; Neuss, Michael; Lichtenauer, Michael; Haase-Fielitz, Anja; Butter, Christian; Edlinger, Christoph (Frontiers in Cardiovascular Medicine, 2024)
Background: Severe tricuspid regurgitation is a progressive disease with an unfavourable prognosis. In recent years there have been extraordinary gains in knowledge through both clinical and basic scientific work. We performed a bibliometric analysis on tricuspid regurgitation with a focus on imaging techniques and treatment approaches and to identify scientific milestones and emerging research trends. Methods: Publications, published between 2015 and 2023 were identified. Study characteristics, impact factors and countries of origin studies were recorded. Heat maps were created to visualise data and to identify leading centers. Most frequently cited publications were recognised as milestones. Results: We screened 3519 studies. 368 studies were included, of which 326 were clinical studies. Clinical studies were further subdivided into interventional (n=138), surgical (n=115) or studies on imaging modalities (n=74). We detected an enormous increase in scientific output worldwide, especially in imaging and interventional studies. The United States, Germany and Poland were identified as leading countries in imaging, interventions and preclinical studies respectively. Conclusions: Our study reflects the global gain in knowledge over the last 9 years. We were able to identify an annually rising number of interventional studies. Imaging studies have also seen a rapid increase, especially since 2020. In recent years, we monitored a decline in surgical studies.